A practical guide to mentoring : using coaching and mentoring skills to help others achieve their goals - Kay, David, 1941-; Hinds, Roger, 1940- (Oxford, England : How To Books, 2012)
Mentoring can be such a rewarding experience. You will play an active and invaluable part in the development of another person and further your own career at the same time. Whichever sector you work in, this effective book will clarify the whole mentoring process from start to finish, and support you every step of the way.
Includes index.
Previous edition : 2009.
Keywords: Mentoring in business; Mentoring